REASONS FOR THE PREVALENCE OF SMOKING AMONG UNIVERSITY STUDENTS AND RECOMMENDATIONS FOR REDUCING THE PREVALENCE (Physical Culture and Sport: Scientific Perspective, 2025)
The problem of tobacco use is bigger and deeper than the public knows. Every 10 seconds, one person in the world dies as a result of tobacco use. The power of nicotine addiction is equal to or greater than heroin and cocaine addiction, much stronger than addiction to alcohol, cannabis or LSD and other similar drugs. And this is not a problem of smokers alone, but rather a problem of those around them. Therefore, it should be solved not even at the state level, but at the social level. After all, methods to overcome nicotine addiction are necessary for normal life not only for smokers, but for all people. In fact, humanity engages in tobacco smoking precisely because it is unable to timely satisfy its crying needs with life-giving methods or is unaware of its need for life-giving methods. In the modern literature, we have identified 5 methods of overcoming nicotine addiction: educational, prohibition, medication, emotional, and positive reinforcement. Most of these popular methods do not work because their authors and promoters do not think about the fact that tobacco smoking satisfies some crying needs of the smoker, and until the smoker starts to satisfy these crying needs in another, life-giving way, he or she will not quit.  The urgent needs of a smoker who started smoking at university: 1. Elimination of stress and fatigue; 2. Ability to organize their thoughts in conditions of overloaded intellect; 3. Getting pleasure; 4. Deepening communication. To meet these needs, relaxation techniques should be taught as the first discipline in secondary schools until practical skills are acquired.  Five-minute relaxations should be used at least twice per class, and this will not be a waste of academic time, since it is not how much the teacher has taught per class that matters, but how much the students have learned, and the ability to perceive directly depends on relaxation. The programs are overloaded with theory, and it should be reduced in favor of physical activity, which is an excellent substitute for tobacco smoking if properly organized. It is imperative to include in the secondary school curriculum a lecture on the hormones of happiness and life-giving methods of regulating them, as well as practical exercises that will teach students how to do so. Then the issue of satisfying their needs in destructive ways will not be on the agenda for young people.
Keywords: smoking; student; overcoming nicotine addiction; causes of smoking; methods of overcoming nicotine addiction; educational; prohibitive; medicinal; emotional; positive reinforcement; life-giving methods